Nur Algorithm on Data Encryption and Decryption - Aminudin, Nur; Maseleno, Andino; K, Shankar; Hemalatha, S; Sathesh kumar, K; ., Fauzi; Irviani, Rita; Muslihudin, Muhamad (International Journal of Engineering and Technology, 2018)
Security is a priority in information system, especially in the exchange of data that are important or confidential. The information to be given to the party entitled to the information must be properly safeguarded, don’t fall into the  other hands who have no right to such information. One way to maintain the security of information exchanged in a system can be done using cryptographic techniques. Cryptography is the art and science to hide information from third parties. In cryptography a person who has a private key can convert plaintext data into unique and unreadable data (ciphertext) and can convert existing ciphertext into plaintext form by using its private key. System development (System Development Lifecycle) can mean to construct a new system to replace old system, combined with prototyping technique to build a cryptographic system using Nur algorithm which is implemented using programming language used is assembly (MASM32). In Nur Aminuddin's Encryptor there are two data-reading techniques namely encryption technique (the technique of converting data from the original into unreadable code) and decryption technique (the techniques of reading unreadable codes become readable) Encryption technique is built by applying technique of modern cryptography which holds secrecy on the symmetric key, so the security of encryption depends only on the key and does not depend on whether the algorithm is known to people or not.